Faktor-Faktor yang Mempengaruhi Penggunaan Kontrasepsi Implant - Erma Sugiana; ST Aisjah Hamid; Erma Puspita Sari (Universitas Batanghari Jambi, 2021)
The implant is an effective and efficient hormonal contraceptive in the form of a rod that is implanted under the skin in the upper arm, and the protection period can be up to five years. The purpose of this study was to determine the factors that influence implant contraceptive use. This research is an analytical survey with a cross sectional research design, the study was conducted in June - August 2020 at Puskesmas Gumawang Kab. Oku Timur South Sumatra. The population in this study were all couples of childbearing age who used family planning who visited the Puskesmas in Puskesmas Gumawang Kab. East Oku, which is estimated to be 7,729 acceptors and the sample used in this study were some of the mothers who used family planning who visited the UPTD Puskesmas Gumawang Kab. East Oku in 2019, amounting to 99 people, through Proportional Random Sampling, univariate (proportion), bivariate (chi square test) and multivariate (logistic regression) analysis. The results of the analysis showed that parity (p value: 0.004) and age (p value: 0.028), occupation (p value: 0.001), had a significant relationship with the use of family planning implants, while education (p value: 0.089) had no significant relationship with use of implant birth control. Based on the final model of multivariate analysis, the variable that has the greatest influence on the use of implant family planning is the occupational variable. It is hoped that the results of this study can increase the active role of midwives to provide IEC about the advantages and disadvantages of contraceptive methods that acceptors will choose according to their goals and age.